Enhancing Medical Student Education by Implementing a Competency‐Based Ophthalmology Curriculum. Issue 1 (January 2017) - Succar, Tony; McCluskey, Peter; Grigg, John
Abstract : Purpose: : To evaluate innovative educational strategies that help optimize ophthalmology teaching in a crowded medical curriculum. The knowledge acquisition and perceptions of medical students undertaking the revised competency‐based curriculum were compared with the prior content‐based curriculum within the Sydney Medical Program. Design: : A mixed‐methods research design was employed to include both quantitative and qualitative dimensions in evaluating the revised curriculum with medical students (n = 328) undergoing their ophthalmology rotation. Methods: : Quantitative evaluation was performed with a 20‐item multiple choice pre‐ and post‐test of ophthalmic knowledge. A 12‐month follow‐up test was readministered to compare the long‐term retention rate of graduates. Qualitative evaluation was measured with student satisfaction questionnaires. Results: : In the original curriculum there was an improvement of 19.9% from pre‐ to post‐test scores [2.15; 95% confidence interval (CI), 1.35‐2.94; P < 0.001] and a greater improvement of 31.6% from pre‐ to post‐test (3.50; 95% CI, 3.03‐3.97; P < 0.001) in the revised curriculum. When assessing retained knowledge at 12 months, students from the revised curriculum scored 11.5% higher than students from the original curriculum (1.56; 95% CI, 0.42‐2.71; P = 0.008). In addition, qualitative feedback also improved, with the rotation being highly valued. Conclusions: : The revised ophthalmic curriculum resulted in an increase in academic performance and a higher degree of student satisfaction. Given the gradual decline of ophthalmic education in the standard medical school curriculum, our results are timely in providing guidance for minimum ophthalmic curriculum exposure and strategies to improve ophthalmic education in medical schools.